Development of an e-health education program at the workplace using formative research – Technologies for improving quality of life. (April 2019) - Maciel, Roberto Rodrigues Bandeira Tosta; Chiavegato, Luciana Dias; Marin, Luz Stella; Portella, Daniel Deivson Alves; de Souza, Marcio Costa; Camelier, Fernanda Warken Rosa; Padula, Rosimeire Simprini
Highlights: The success of an e-health program depends on the abilities of the staff members. This paper describes the use of formative research to identify education needs. The focus group method allowed development of an e-health education program. Abstract: Background: e-Learning, a means by which to expand people's access to information can be effective in promoting health in the workplace. This study to present steps in the development of an e-health education program at the workplace. Objective: This study aimed to present all steps of develop a telehealth education program for computer users using formative research to identify themes to health education for workers. Methods: A team of expert conducted focus groups with administrative workers (n = 36 participants) to identify thematic health to the development of program. Three meetings were audio video recorded, and notes. All data were based on constant analysis, classical content analysis and keywords in-context. Results: The content of the nine audio videos included four musculoskeletal health topics (Walking Program, Back School, Muscle Relaxation Techniques, and Work-related Musculoskeletal Diseases); three to healthy diet (Eating and Commensality, Ultra-processed Food and Food labeling, and Oil and Fat); two to mental health (Burnout Syndrome and the Meaning of work). Conclusion: The proposed steps in the development of a workplace e-health education program were successfully achieved. The engagement of the workers' staged focus groups was fundamental to the choice of themes relevant to the population in question.